P0917N-ACETYL CYSTEINE FAILS TO IMPACT ON PLASMA ANTIOXIDANT CAPACITY IN BOTH A PLACEBO CONTROLLED CROSSOVER STUDY AND A PARALLEL GROUP TRIAL OF PATIENTS WITH CKD STAGE III: IMPLICATIONS FOR ITS USE AS A PROPHYLACTIC FOR CONTRAST INDUCED NEPHROPATHY. (6th June 2020) - Raja, Khuram; Hickson, Kirsty; Treweeke, Andrew; Rushworth, Gordon; Morrison, Emma; Sandilands, Euan; Cobley, James; McEneaney, David; Eddleston, Michael; Megson, Ian
Abstract: This project has been funded by the EU's INTERREG VA programme, managed by the special EU Programmes Body (SEUPB) Background and Aims: N-acetyl-L-cysteine (NAC) has been proposed as a prophylactic for the prevention of contrast induced nephropathy (CIN), a serious, adverse complication following administration of contrast media in patients with diabetes and chronic kidney disease (CKD). However, clinical trial results have failed to demonstrate consistently the beneficial qualities of NAC in this setting. The suggested mechanism by which NAC has been proposed to be effective is via antioxidant activity, but NAC itself appears not to be a powerful antioxidant; intracellular conversion of NAC to glutathione (GSH) is essential for antioxidant effects. We tested the hypothesis that oral or intravenous NAC fails to increase antioxidant activity in the plasma of healthy volunteers or CKD stage III patients undergoing elective coronary angiography. Method: 16 healthy volunteers (8 receiving contrast media) and 8 patients with chronic renal failure were recruited to 3 separate groups as a part of a crossover design study. 66 patients with CKD stage III undergoing elective coronary angiography were recruited to a parallel group randomized controlled trial. Each volunteer or patient was randomised to receive NAC (i.v.; 50 mg/kg/hr infusion for 2 h, followed by 20 mg/kg/hr infusion for a further 5 h), or NAC (oral; 1200 mg twice daily, commencing the day before the study visit) or placebo. Participants attended the Clinical Research Facility on three occasions for the crossover groups, but only once in the parallel group trial. Patients were infused with para-aminohippurate (PAH) and inulin to enable measurement of renal function parameters. Plasma and paired buffy coat samples were collected at several time points for 2 hours before contrast infusion and for 6 hours after. Samples were used to measure various clinical parameters, along with intracellular and plasma thiol concentrations and the plasma antioxidant capacity (oxygen radical antioxidant capacity; ORAC). Results: Plasma NAC concentrations peaked at 222 µM (healthy volunteers), 354 µM (CKD patients), 271 µM (healthy volunteers receiving contrast) and 348 µM (CKD patients undergoing elective coronary angiography) following infusion of NAC. The corresponding peak concentrations were ∼2 µM following oral NAC across all groups. No comparable increase in the plasma compartment ORAC antioxidant capacity was measured in any of the treatment groups. Equally, contrast infusion itself did not significantly reduce antioxidant capacity in plasma, even in the placebo group. Buffy coat measures showed that there was a significant increase of intracellular GSH in some patients. Also, no clear additional benefit was witnessed by increasing plasma NAC ∼100-fold through infusion of NAC over oral administration. Conclusion: NAC fails to influence ORAC antioxidant capacity in the plasma compartment of CKD stage III patients receiving contrast media. Our results question the importance of oxidative stress in contrast-induced nephropathy. Furthermore, the findings fail to demonstrate a direct antioxidant impact of NAC in the plasma compartment and question the antioxidant hypothesis related to contrast-induced nephropathy and NAC.